PENGARUH METODE EKSTRAKSI TERHADAP AKTIVITAS ANTIMIKROBA EKSTRAK METANOL DAUN MIMBA (Azadirachta indica Juss) - Gemy Nastity Handayany (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2016)
An investigation of the influence of extraction method on theantimicrobial activity of methanol extract of leaves of neem (Azhadirachtaindica Juss) against multiple microbes. This study aims to determine theextraction method that produces extracts that can provide the bestantimicrobial activity. Extraction methods used include maceration,soxhletasi, and reflux using methanol solvent. Tests conducted by inhibitionscreening test, the maceration method inhibits Staphylococcus aurus,thyposa Salmonella, Staphylococcus epidermidis, Streptococcus mutans,Vibrio sp, Escherichia coli, Bacillus Subtilis and Pseudomonas aeroginosa,whereas Staphylococcus aurus soxhlet method, thyposa Salmonella,Staphylococcus epidermidis, Streptococcus mutans, Vibrio sp, Escherichiacoli, and Pseudomonas aeroginosa, and reflux methods aurusStaphylococcus, Staphylococcus epidermidis, Vibrio sp, Escherichia coli andPseudomonas aeroginosa. Minimum inhibitory concentration test, themethods of maceration, soxhlet and reflux in a row that the bacteriumEscherichia coli to produce 0.05%, 0.1%, and 0.2%, while the bacteriumStaphylococcus aureus, 0.05%, 0.2% and 0.2%. Minimum kill concentrationtest, the methods of maceration, reflux, and Soxhlet, respectively, namely thebacterium Escherichia coli and Staphylococcus aureus produce 0.2%, 0.4%and 0.4%. Test medium agar diffusion method using Glucose Nutrient Agar(GNA). Antimicrobial activity test results show that the largest amount ofinhibition zone on the test bacteria Escherichia coli and Staphylococcusaureus maceration method.